2016
DOI: 10.1016/j.jpeds.2015.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Buspirone for Restricted and Repetitive Behavior in Young Children with Autism Spectrum Disorder: A Randomized Trial

Abstract: ClinicalTrials.gov: NCT00873509.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 54 publications
(48 reference statements)
0
46
0
1
Order By: Relevance
“…While some have suggested that the female Fmr1 KOs should be included in studies with males based on similarity, here we highlight the marked phenotypic differences, and as such, future research could focus on how these phenotypes could, and should, be treated separately. For instance, repetitive behavior phenotypes are commonly treated using several different types of drugs, including 5‐HT1BR agonists (Ho et al., 2016), 5HT1A partial antagonists (Chugani et al., 2016) and more recently, antioxidants (Hardan et al., 2012). Through the routine exclusion of females from biomedical studies, opportunities are missed to explore potential treatments and how sex may impact the efficacy of such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…While some have suggested that the female Fmr1 KOs should be included in studies with males based on similarity, here we highlight the marked phenotypic differences, and as such, future research could focus on how these phenotypes could, and should, be treated separately. For instance, repetitive behavior phenotypes are commonly treated using several different types of drugs, including 5‐HT1BR agonists (Ho et al., 2016), 5HT1A partial antagonists (Chugani et al., 2016) and more recently, antioxidants (Hardan et al., 2012). Through the routine exclusion of females from biomedical studies, opportunities are missed to explore potential treatments and how sex may impact the efficacy of such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mice lacking brain 5-HT, in addition to several abnormal phenotypes (growth retardation, high aggressive behavior, maternal neglect), show selective deficits resembling ASD's symptoms, including impairments in social interactions and repetitive behavior [3,4]. Various pharmacological studies are providing evidence that targeting 5-HTRs has the potential to treat the core symptoms of ASD and associated intellectual disabilities [91][92][93][94]. Recent evidence in animal models suggest that, among other subtypes, the 5-HT7R might be one of the players involved in ASD (see below).…”
Section: The 5-ht7r and Neurological Diseasesmentioning
confidence: 99%
“…A recent Autism Speaks sponsored working group panel recommended the Vineland‐II as suitable (having adequate reliability, validity, and responsiveness) to quantify social communication deficits in clinical trials of ASD [Anagnostou et al, ; see also McConachie et al, ]. The Vineland‐II is also increasingly used in randomized trials targeting core ASD symptoms and/or adaptive behavior more broadly [e.g., Chugani et al, ; Dawson et al, ; Hardan et al, ; Scahill et al, ; Umbricht et al, ; Veenstra‐VanderWeele et al, ; Ventola et al, ], in part due to the relative lack of other reliable measures of change in these behaviors [Anagnostou et al, ]. This increasing use may also reflect the relatively broader scope of adaptive behaviors assessed by Vineland‐II, relative to the more circumscribed set of core ASD symptoms (McDougall et al, in press).…”
Section: Introductionmentioning
confidence: 99%